P-D5 Synthesis and characterization of core-–shell silica cobalt ferrite nanoparticles as a first step towards developing ultrasensitive MRI probes for long-acting antiretroviral drug biodistribution testing. (March 2017) - Kevadiya, Bhavesh; Bade, Aditya; Woldstad, Christopher; Boska, Michael; Edagwa, Benson; Mcmillan, Joellyn; Gendelman, Howard
Abstract : Cobalt ferrite (CF) nanoparticles were developed as magnetic resonance (MR) imaging contrast agents. However, its size, shape and chemical features also make the particles applicable for screening biodistribution of drug carriers. In developing long-acting nanoformulated antiretroviral drugs (ARVs), CF provides unique translational prospects. Thus, we investigated whether europium (Eu) doped CF nanoparticles (CFEu) could be useful in screening of nanoparticle ARVs. CFEus were synthesized by a modified solvothermal technique and functionalized with core-shell-Pluronic®F-127 (Si-CFEu). The synthesized superparamagnetic, monodispersed CFEus were highly crystalline with an inverse-spinel structure. The particle size was 7.2 nm and 140 nm for CFEu and Si-CFEu, respectively. Folic acid (FA) decoration onto the surface of the Si-CFEu facilitated mononuclear phagocyte (MP) targeting. Uptake and retention of FA-Si-CFEu nanoparticles by MP were demonstrated. The presence of intracellular particles was made by prussian blue and confocal microscopy confirming the ultrahigh transverse relaxivity (r 2 = 7917.9 s/mL/μg) measurements. To simulate immune activation of HIV-1- infected person, rats were treated with 2 mg/kg lipopolysaccharide (LPS). MRI scans demonstrated increase in T2 and decrease in signal in the reticuloendothelial system of the LPS treated rats 24 hours post-injection of Si-CFEu and FA-Si-CFEu. FA-Si-CFEu particles provided significantly higher tissue iron concentration compared to Si-CFEu signifying targeting abilities. These data bring us one step closer towards using decorated Si- CFEu particles to assess biodistribution of nanoformulated ARVs.